Consequences of fashion diets on women's health (Research, Society and Development, 2023)
The article aims to demonstrate, through a literary review, the consequences that diets made under the influence of the various existing social media platforms can impact women's health, given that the search for the ideal body in a short period of time has increasingly intensified. , it is clear that the media interferes significantly in the actions of individuals related to eating behavior, the majority of this group in question first goes through social networks before looking for a professional who is actually qualified in the area, these abrupt changes in eating behavior can generate serious physical, emotional and psychological consequences, we can highlight the main ones being eating disorders, such as bulimia, anorexia, low self-esteem, distortion of body self-image, they can generate food intolerances that did not exist before, in some cases they can even lead to death. restricting one or more food groups is common in the diets mentioned in this article, and most of these prohibitions do not have any scientific support. the main objective of this research is to emphasize that the adoption of popular diets by the lay public, without proper guidance from a nutritionist, can impose risks and harm to health, that this whole scenario associated with the speed of circulation of information causes even more the growth of eating disorders and the globalization of beauty standards that are beyond the reality of many women.